Analysis of patients with obstructive sleep apnea with and without pharyngeal myopathy using brain neuroimaging - Baima, Camila Bonfanti [UNESP] (2020)
Study Objectives: Elements impairing upper airway anatomy or muscle function (e.g. pharyngeal neuromyopathy) contribute to obstructive sleep apnea syndrome (OSAS). Structural brain imaging may differ in patients with OSAS according to dilator muscle dysfunction. Magnetic resonance imaging (MRI) with voxel-based morphometry (VBM) and surface-based morphometry (SBM) was used to investigate this hypothesis. Methods: Eighteen patients with OSAS and 32 controls underwent 3T brain MRI. T1 volumetric images were used for structural analysis. Pharyngeal electroneuromyography was performed; patients with OSAS were classified as with or without neuromyopathy. VBM and SBM analyses were conducted using SPM12 and CAT12 software. Image processing was standard. Cortical surface parameters and gray and white matter volumes from participants with OSAS with and without neuromyopathy were compared with those from controls. Results: Eleven patients had OSAS with neuromyopathy and seven patients had OSAS without neuromyopathy (normal pharyngeal electroneuromyography). Comparing these groups to the controls, VBM revealed: four clusters (total volume 15,368 mm3) for patients with neuromyopathy, the largest cluster in the left cerebellum (9,263 mm3, p = 0.0001), and three clusters (total 8,971 mm3) for patients without neuromyopathy, the largest cluster in the left cerebellum (5,017 mm3, p = 0.002). Patients with OSAS with neuromyopathy showed increased proportion of atrophy (p < 0.0001). SBM showed abnormalities in patients without neuromyopathy (decreased cortical thickness, left precentral gyrus [672 vertices, p = 0.04]; increased cortical complexity, right middle temporal gyrus [578 vertices, p = 0.032]). Conclusion: Damaged areas were larger in patients with OSAS with than in those without neuromyopathy, suggesting differences in brain involvement. Patients with OSAS and neuromyopathy may be more susceptible to cerebral damage.